Aetiology, epidemiology and treatment of musculoskeletal injuries in badminton players: a systematic review and meta-analysis - Marchena-Rodriguez, A.; Cabello-Manrique, D.; Ortega-Avila, A. B.; Martinez-Rico, M.; Cervera-Garvi, P.; Gijon-Nogueron, G. (Research in Sports Medicine, 2024)
The present study has two main goals: to conduct a systematic review of musculoskeletal injuries experienced by badminton players, and to examine the management of such injuries. Searches were conducted of the PROSPERO, PubMed, Scopus, and SPORTDiscus databases, from their inception until March 2023. The papers analysed were all based on a study population consisting of individuals aged 18 years or more, diagnosed with badminton-related injuries. The methodological quality assessments was using the Newcastle-Ottawa Scale and REVMAN. A total of 28 studies were included in the systematic review. In total, the analysis included 2435 participants. Of these athletes, 35.6% (1012) were female and 64.4% (1503) were male. By type of injury, sprains were the most commonly studied and the most prevalent, accounting for 36.06% of the sample. These were followed by muscle injuries, representing 23.86% of the total. Injuries to the joints were the least prevalent, accounting for 4.97% of the sample. Lower limb injuries accounted for 52.15% of the total. Of these, ankle injuries were the most common. Despite the generally low quality of the studies considered, the evidence suggests that musculoskeletal injuries, especially to the lower limb, most commonly affect badminton players of all levels.